Aquatic insect biodiversity and water quality parameters of streams in Northern Thailand - Prommi, T.; Payakka, A. (Universiti Kebangsaan Malaysia, 2015)
Biodiversity of aquatic insect and physicochemical water quality parameters in Mae Tao and Mae Ku watersheds were assessed bi-monthly from February 2011 to February 2012. A total of 59 families representing 9 orders were recorded. At order level, Trichoptera was found at the highest frequency in total abundance (45.75%) followed by Ephemeroptera (18.06%), Hemiptera (13.45%), Odonata (9.62%), Diptera (8.17%), Coleoptera (4.6%), Megaloptera (0.17%), Lepidoptera (0.11%) and Plecoptera (0.07%). The family Hydropsychidae was the most prominent and the most abundant aquatic insect taxa followed by Chironomidae. Water temperature, dissolved oxygen and ammonia-nitrogen were similar at all sampling stations. Significant variations in pH, electrical conductivity, total dissolved solids, sulfate, nitrate-nitrogen and alkalinity were found at all sampling stations. Taxa richness and diversity index significantly correlated with dissolved oxygen, sulfate, nitrate-nitrogen and ammonia-nitrogen (p<0.05, p<0.01). Physicochemical data and biological data showed that mostly the surface water quality in Mae Tao and Mae Ku watersheds were within Type III of The Surface Water Standard for Agriculture and Water Quality for Protection of Aquatic Resources in Thailand.